Teacher Training to Address Difficulties in Using Problem-Based Learning Models in Mathematics Instruction for Fifth-Grade Students at SD N 1 Wonogiri - Farid Cahyo Wibowo; Achmad Fathoni (Journal of Educational Sciences, 2026)
This study examines teacher training to overcome obstacles in implementing Problem-Based Learning in fifth-grade mathematics at SD Negeri 1 Wonogiri, with an initial average score of 70 and teaching still based on lectures. The purpose of this study is to describe teacher readiness, training implementation, and the results of PBL implementation in fifth-grade mathematics at SD Negeri 1 Wonogiri. This study used a descriptive qualitative approach, with data collected through interviews and observations of teachers and the principal. The findings showed that before the training, teachers were highly motivated but limited in PBL syntax, contextual problem design, and facilitating group discussions. After the training, teachers showed concrete behavioral changes, such as consistently applying the PBL stages, asking provoking questions, and using contextual problems relevant to the local environment. Structured and practice-based PBL training resulted in noticeable improvements in teachers' readiness and confidence. Post-training PBL implementation followed a more systematic pattern from problem orientation to reflection, which was associated with increased student participation, active engagement in group discussions, and understanding of mathematical concepts through problem solving. However, time constraints and differences in student abilities remained challenges.